Therapeutic ultrasound in fracture healing: The mechanism of osteoinduction - John, P S (Medknow Publications, 2008)
BACKGROUND: Ultrasound has been used therapeutically for accelerating fracture healing since many years. However, the controversy on the exact mechanism of osteoinduction still continues. In this study, we try to bring out the exact biomolecular mechanism by which ultrasound induces fracture healing. MATERIALS AND METHODS: The study was conducted in two phases: animal experiments and clinical study. In the first phase, we induced fractures on the left tibia of Wistar strain rats under anaesthesia. They were divided into two groups. One of the groups was given low-intensity, pulsed ultrasound (30 MW/cm(2)) 20 min a day for 10 days. Tissue samples and radiographs were taken weekly for 3 weeks from both the groups. In the second phase of our study, ten patients with fractures of the distal end of the radius (ten fractures) were included. Five of these were treated as cases, and five were treated as controls. Ultrasound was given 30 MW/cm(2) for 20 min every day for 2 weeks. The patients were assessed radiologically and sonologically before and after ultrasound therapy. Tissue samples were studied with thymidine incorporation test with and without adding various neurotransmitter combinations. RESULTS: Radiological findings revealed that there was an increased callus formation in the ultrasound group. At the cellular level, there was an increased thymidine incorporation in the ultrasound group. When various neurotransmitters were added to the cells, there was an increased thymidine incorporation in the ultrasound group. In the second phase of the study, radiological and sonological assessments showed that there was an increased callus formation in the ultrasound group. In cytological study, thymidine incorporation was found to be increased in the ultrasound group. CONCLUSIONS: The results of animal and clinical studies demonstrated an early and increased callus formation in the ultrasound group. Cytological studies revealed increased thymidine incorporation, suggesting increased osteoblastic activity.